Reef fish antipredator behavior in remote islands does not reflect patterns seen in coastal areas. Issue 6 (2nd November 2019) - Nunes, José Anchieta C.C.; Blumstein, Daniel T.; Giglio, Vinicius J.; Barros, Francisco; Quimbayo, Juan P.
Abstract : The reduction or loss of antipredator behavior is expected for animals isolated on islands, but most of studies have focused on terrestrial rather than aquatic species. Two different processes may modulate fish antipredator behavior in the waters off remote archipelagos. First, places with low human density may have reduced fishing pressure. Second, due to their remoteness and lack of other human impacts, these isolated places may have more intact fish assemblages. We investigated antipredator behavior off the smallest archipelago in the Equatorial Atlantic not subjected to regular spearfishing by quantifying flight initiation distance (FID) ― the distance a diver can approach a fish before it flees. Our goal was to identify natural patterns of risk assessment in reef fish. We focused on five common species and investigated how body size, group size and depth influence on the FID. In contrast to previous studies, we found that Caranx lugubris had significantly negative relationships between body size and FID, whereas Kyphosus sectatrix showed an opposite relationship. Finally, only a single species ( Melichthys niger ) had a significant relationship between depth and FID. Given we found small FID for all species studied, we suggest that much of our understanding of fish antipredator behavior studied using FID may reflect the somewhat ubiquitous impact of humans on species' risk assessments and not reflect patterns seen in areas with very low human density/disturbance. Our results suggest that fish antipredator behavior may be a metric of human impacts.